The efficacy of adding oral sodium cromoglycate to stable treatment for controlling bullous pemphigoid-related pruritus: A retrospective study - Keller Rosenthal, Noy; Boucher, Darby; Murrell, Dedee F. (Frontiers in Medicine, 2022)
Introduction Bullous pemphigoid (BP) is the most common autoimmune subepidermal blistering disease which mainly affects the elderly. It manifests as severe pruritus, urticarial plaques, and tense bullae and is associated with significant mortality. Therapy options for itch in BP patients are limited, mainly because the pathogenesis of itch in BP remains unclear. Sodium cromoglycate was commonly used in the past as an inhaled drug for the management of bronchial asthma and as an oral treatment for children with urticaria pigmentosa. In this study we sought to assess its efficacy in reducing BP associated itch. Objective Assessing the efficacy of oral sodium cromoglycate in reducing BP-related pruritus after stabilization of disease activity. Methods We retrospectively reviewed the medical records of patients with a confirmed diagnosis of BP who were treated with sodium cromoglycate. Patient reported outcome measures (PROM) including: BPDAI pruritus, ABQOL and TABQOL, and BPDAI activity score were compared at two points in time: before commencing treatment with sodium cromoglycate or before commencing maximal dose of this treatment, and at least 4 weeks after treatment commencement. Results A total of 21 patients met the inclusion criteria. After at least 4 weeks of treatment with oral sodium cromoglycate BPDAI pruritus, ABQOL and TABQOL scores were statistically significantly decreased compared to the scores prior to treatment commencement, P < 0.000, P < 0.008, and P < 0.004, respectively. Discussion Oral treatment with sodium cromoglycate for the management of pruritus in BP patients may be beneficial, however, further prospective studies are required to better assess its efficacy.